Case Report: Potential role of selective venous sampling for liquid biopsy in complex clinical settings: Three case presentations - Tichà, Vladimira; Patelli, Gianluigi; Basso, Gianpaolo; Prino, Aurelio; Repetti, Elena; Grugni, Maria; Damascelli, Bruno (Frontiers in Genetics, 2023)
Tumor mutation profiling from a blood sample is a reality that has already been approved for some cancers. So-called liquid biopsy is a molecular diagnostic method that complements tissue biopsy but is less invasive and therefore more easily applied, especially during tumor evolution. Its use should allow detection of residual disease, evaluation of treatment response or resistance, and selection of targeted treatments. However, implementation of liquid biopsy in routine clinical practice is hindered by unsolved issues, one of which is the scarcity of circulating tumor DNA in blood samples drawn from peripheral veins. To address this problem, we propose minimally invasive selective venous sampling from the region of interest, as used for some hormonal studies and for mapping of endocrine tumors. Intuitively, selective sampling should improve the sensitivity of liquid biopsy by avoiding the dilution of tumor biomarkers that occurs in the peripheral circulation. We report three cases that illustrate the potential utility of selective liquid biopsy in complex clinical settings, providing implications for diagnosis and treatment as well as for monitoring over time, disease localization, identification of drug resistance, and differential diagnosis.